1997
DOI: 10.1016/s0003-4878(97)00005-7
|View full text |Cite
|
Sign up to set email alerts
|

Volatilisation processes in wastewater treatment plants as a source of potential exposure to vocs

Abstract: The results of a survey estimating volatilisation rates (as gas exchange constants and flux rates) of a range of hazardous alkane, aromatic, organohalogen, organosulphide, ketone and alcohol volatile organic compounds (VOCs) from a water bay are presented. More than 73 experimental test runs were earned out over a year under varying seasonal conditions to measure the simultaneous concentrations of VOCs in air and water phases. The data were processed employing new advances in 'surface renewal' volatilisation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…6, the experimental evaporation trend very closely followed the extrapolated trend at 1.58 m/s wind velocity. According to Bianchi and Varney (1997), a flux transfer rate for the VOCs is a function of wind speed and VOC concentration differences between air and water phases. In case of our experiments at the low-wind condition, the velocity of wind (0.54 m/s) might not have been efficient in the removal of TCE molecules, resulting in TCE concentrations above the water surface.…”
Section: Influence Of Wind On Evaporationmentioning
confidence: 99%
“…6, the experimental evaporation trend very closely followed the extrapolated trend at 1.58 m/s wind velocity. According to Bianchi and Varney (1997), a flux transfer rate for the VOCs is a function of wind speed and VOC concentration differences between air and water phases. In case of our experiments at the low-wind condition, the velocity of wind (0.54 m/s) might not have been efficient in the removal of TCE molecules, resulting in TCE concentrations above the water surface.…”
Section: Influence Of Wind On Evaporationmentioning
confidence: 99%
“…Although several papers have focused on the monitoring of VOC emissions in industrial facilities [10][11][12][13][14][15], the emissions of VOCs from wastewaters in industrial-sewage treatment plants are often overlooked as sources of hazardous substances. Previous papers have shown the influence of urban WWTP emissions on air quality [16][17][18][19][20][21]. However, there are only a few studies on the composition of industrial WWTP emissions [22,23] and their relative importance as a potential source of specific hazardous air pollutants must be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the methods that have been developed for determining VOC emissions from urban and industrial WWTPs are either canister-based [11,22] or sorbent-based [16,18,19,21,23]. New trends in VOC determination focus on the development of versatile, portable, low-cost and environmentally-friendly techniques without compromising the limit of detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, we observed that, when very complex mixtures are analyzed (gaseous emissions from wastewater treatment plants contain hundreds of different compounds [15,16]), the sensor responses are strongly correlated, and their temperature dependence is not clearly definable.…”
Section: Electronic Nose Descriptionmentioning
confidence: 94%